2010
DOI: 10.1101/cshperspect.a003889
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome Territories

Abstract: Chromosome territories (CTs) constitute a major feature of nuclear architecture. In a brief statement, the possible contribution of nuclear architecture studies to the field of epigenomics is considered, followed by a historical account of the CT concept and the final compelling experimental evidence of a territorial organization of chromosomes in all eukaryotes studied to date. Present knowledge of nonrandom CT arrangements, of the internal CT architecture, and of structural interactions with other CTs is pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

48
837
0
7

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 981 publications
(892 citation statements)
references
References 120 publications
48
837
0
7
Order By: Relevance
“…FISH chromosome painting using preserved nuclei of wild-type spermatocytes revealed that chromosome 8 homologs occupy spatially limited territories during meiotic prophase, as previously reported in human spermatogonia ( Fig. 1C; Scherthan et al 1996), which is similar to the chromosome territories observed in interphase somatic cells (Cremer and Cremer 2010). Although most homologs are separated from each other during premeiotic S phase, some homologs start to locate in close proximity to one another (juxtaposed) at the early leptotene stage (Fig.…”
Section: Homolog Pairing Initiates In Early Leptotenementioning
confidence: 49%
“…FISH chromosome painting using preserved nuclei of wild-type spermatocytes revealed that chromosome 8 homologs occupy spatially limited territories during meiotic prophase, as previously reported in human spermatogonia ( Fig. 1C; Scherthan et al 1996), which is similar to the chromosome territories observed in interphase somatic cells (Cremer and Cremer 2010). Although most homologs are separated from each other during premeiotic S phase, some homologs start to locate in close proximity to one another (juxtaposed) at the early leptotene stage (Fig.…”
Section: Homolog Pairing Initiates In Early Leptotenementioning
confidence: 49%
“…Among these technologies are chromosome conformation capture (3C) (1) and its several iterations, such as Hi-C (2), which are applied to populations of nuclei to identify chromosomal regions that are in close proximity to each other (3,4). Another technology is fluorescence in situ hybridization (FISH), wherein nucleic acids are targeted by fluorescently labeled probes and then visualized via microscopy; this technology is an extension of methods that once used radioactive probes and autoradiography but have since been adapted to use nonradioactive labels (5)(6)(7)(8)(9)(10)(11). FISH is a single-cell assay, making it especially powerful for the detection of rare events that might otherwise be lost in mixed or asynchronous populations of cells.…”
mentioning
confidence: 99%
“…These novel bioimaging methods have been employed to study the complex chromatin organization, which span several orders of magnitude to save genetic information on the mix of DNA and proteins, and to verify that organizational units, for example, domains with similar size as TADs, do exist in 3D genome [112]. However, it is challenging to employ SR microscopy to study the relationship between 3D genome organization and the regulation of gene transcription.…”
Section: Resultsmentioning
confidence: 99%